The Effect of Implementing the Family Centered Care Method on Hospitalization Stress in Children Aged 3-6 Years - Nur Laela (CV, Akira Java Bulu, 2025)
Being sick and being hospitalized is a major crisis in children who are hospitalization. Family centered care is one way to reduce the stress level of hospitalization in children. The purpose of this study was to determine the effect of applying the family centered care method to hospitalization stress in children. Method: This was a quantitative experiment with the design of pre-post test with control group design. The collection of data was done using a stress level questionnaire and the FCCAS questionnaire. The number of respondents was 48 pediatric patients with a total consecutive sampling technique. The data obtained were then processed statistically using the Wilcoxon test and Chi Square test. The results of the analysis obtained that out of 48 children mostly large had the characteristics of the age of 3 years of age, 37.5% with the sex of the majority being female, namely 52.1% and those who had never been hospitalized before, 68.8%. The results of the Wilcoxon test showed that the difference between pre and post stress in the control group was ???? = 0.004 and the intervention group was ???? = 0.001, because the ???? value <0.05, it can be concluded that there was a significant difference between pre and post stress in the control and intervention groups. The results of the Chi Square test obtained a ???? =0.001 (???? -value <0.05). Family centered care is effective in reducing children's stress levels due to hospitalization and is expected to be applied in hospitals and health services to increase family satisfaction and quality of service in hospitals. Future researchers can examine the application family centered care method by developing an Islamic version to reduce children's stress.